ORGANOMETRIC STUDY OF THE UPPER JAW IN THE PERINATAL PERIOD OF HUMAN ONTOGENESIS - Корчинська, Н.С. (World of Medicine and Biology, 2015)
Organometric examination of the upper jaw on 53 dead 4-10-month fetuses have been conducted. Two periods of an accelerated development of the organometric parameters of the upper jaw have been found (for the height – on the 5th and 7th month, for the width – on the 6th and 7th month), as well as two periods of relatively slow development (for the height – on the 6th and 8-10 months and for the width – on the 5th and 8-10 months). Inearly fetuses (4-5thmonth) the longitudinal parameters of the upperjaw, face and cranium en large predominantly, beginning from the 6th month transverse parameters prevail.